KAJIAN HUKUM TERHADAP PENINGKATAN HAK GUNA BANGUNAN MENJADI HAK MILIK DI KABUPATEN WONOGIRI - EMAWATI, ANITA (Dinamika Hukum, 2015)
The research objective is to study and to analyze the building rights improvement to become properties rights in the district of Wonogiri and the legal consequence of the building rights improvement implementation to become properties in the district of Wonogiri. The background of the application of the law, including legal protection of property rights on land with the status alteration to become properties rights based on the applicable Government Regulation, referring to Government Regulation No. 24 year 1997 related Ministry of Agriculture’s decision No. 6 of 1998. Therefore granting property rights to land should be based on the Ministry of Agriculture of No. 6 of 1998 on the granting of property rights to land for house live and regulations that accompany it. It is an aspect of the provision of public welfare in rights improvement. Keyword : Building Rights Improvement to Become Properties Rights